2006
DOI: 10.1002/eji.200636617
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic acid agonists for Toll‐like receptor 7 are defined by the presence of uridine ribonucleotides

Abstract: Toll-like receptor 7 (TLR7) mediates innate responses by responding to viral RNA in endocytic compartments. However, the molecular pattern recognised by TLR7 and whether it differs between RNA of viral and self origin remains unclear. Here, we identify nucleic acids that act as TLR7 agonists for mouse and human cells. We show that uridine and ribose, the two defining features of RNA, are both necessary and sufficient for TLR7 stimulation, and that short single-stranded RNA (ssRNA) act as TLR7 agonists in a seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
166
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(177 citation statements)
references
References 48 publications
(97 reference statements)
8
166
3
Order By: Relevance
“…Imidazoquinolines also interfere with the adenosine and opioid growth factor receptor signaling pathways independent of TLR7 and TLR8 (29,30) Recent studies have shown that synthetic RNAs formulated with lipid carriers also activate TLR7 and TLR8 in a sequence-dependent manner (2,23). However, singlestranded RNA is highly susceptible to nuclease degradation, and the use of lipid carriers has been required to stabilize RNAs against nucleases (12,(31)(32)(33)(34)(35)(36). We have designed RNAs linked through their 3′-ends to prevent 3′-exonuclease degradation, referred to as SIMRA compounds, which act as agonists of TLR7, TLR8, or both TLR7 and TLR8, depending on the nucleotide sequence and chemical modifications incorporated (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Imidazoquinolines also interfere with the adenosine and opioid growth factor receptor signaling pathways independent of TLR7 and TLR8 (29,30) Recent studies have shown that synthetic RNAs formulated with lipid carriers also activate TLR7 and TLR8 in a sequence-dependent manner (2,23). However, singlestranded RNA is highly susceptible to nuclease degradation, and the use of lipid carriers has been required to stabilize RNAs against nucleases (12,(31)(32)(33)(34)(35)(36). We have designed RNAs linked through their 3′-ends to prevent 3′-exonuclease degradation, referred to as SIMRA compounds, which act as agonists of TLR7, TLR8, or both TLR7 and TLR8, depending on the nucleotide sequence and chemical modifications incorporated (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Although the content of U or GU in the RNA molecule seems to be important for both TLR7 and TLR8 activation [21,23,27,28], the specific RNA motif recognized by TLR7 and/or TLR8 has not yet been identified. It was suggested by Diebold et al [29] that the uracil content and motifs in ORNs define the ability of the ORN to act as a TLR7 ligand, whereas the G content is important for TLR8 ligands. The finding of Peng et al [28] that poly-G3 oligonucleotides are recognized by TLR8 fits into this hypothesis.…”
Section: Viral or Synthetic Single-stranded Rnamentioning
confidence: 99%
“…Other immunostimulatory ligands of TLR7/TLR8 that have been described are self-RNA [29,30] and short interfering RNA [31][32][33][34]. Moreover, 2Ј-O-methyl modification of these RNA molecules inhibits TLR7/8-mediated immune activation, thereby paving the way to the development of TLR7/8 antagonists [35][36][37][38].…”
Section: Viral or Synthetic Single-stranded Rnamentioning
confidence: 99%
“…Accordingly, the TLRs involved in the recognition of foreign mRNA -TLR3, TLR7 and TLR8 -are located in the endosomal compartment. As such, especially uridine-rich ssRNA was identified as a strong immune inducer, mainly via stimulation of TLR7 [26,27], whereas dsRNA rather activates TLR3 [28,29]. Generally, mRNA is considered ssRNA, causing the foreign IVT mRNA to be mostly recognized by the structurally homologous TLR7 and TLR8 receptors [26,30].…”
Section: In Vitro Transcribed (Ivt) Mrnamentioning
confidence: 99%